Emerging through Technological Capability: An Overview of India's Technological Trajectory - Amit Shovon Ray (Indian Council for Research on International Economic Relations (ICRIER), 2008)
India's emergence in the world economy over the last decade, has often, in popular discourse, been attributed, at least to a large extent, to its sustained efforts towards technological learning and capacity building. In this paper we present an overview of India's technological trajectory with a view to understanding the nuances of India's technological capability and the role it has played in the process of India's economic progress. Our conclusion is that while India has successfully nurtured its high-end human capital for technological learning and is poised for a smooth transition to a knowledge economy, there has been a tragic neglect of low end human capital investment for productivity gains in mass manufacturing. This can not be ignored while carving out an appropriate technological strategy for India for a sustainable and 'inclusive' growth process.
Keywords: O3; O31; O33; O34; O38; 330; INDIA; TECHNOLOGICAL CAPABILITY; LEARNING; TFP; IPR; Technischer Fortschritt; Standortfaktor; Produktivität; Immaterialgüterrechte; Wirtschaftswachstum; Indien